Development and validation of a cooperating teacher mentoring scale for student teachers - Alia, Leemarc C.; Magday, Ehlrich Ray J.; Palompon, Daisy R. (Institute of Advanced Engineering and Science, 2025)
Teaching internship is a crucial component of teacher education to prepare student teachers for their future careers in education. This study developed and validated an instrument to measure and evaluate the performance of cooperating teachers in mentoring student teachers. Items capturing the concept of teacher mentoring were developed through literature review, interviews, and focus group discussions. The 110-item 5-point Likert scale was given to 265 randomly selected student teachers from higher education institutions in the Philippines. Validity and reliability of the cooperating teacher mentoring scale (CTMS) were tested using exploratory factor analysis (EFA) and reliability analyses. Moreover, EFA showed three-factor structure of the instrument regarding the CTMS. The study reported the average variance extracted (AVE), composite reliability, and Cronbach alpha coefficients. These findings confirmed that the extracted constructs possess convergent validity and meet the necessary requirements. The item remained in the factor loadings of less than 0.50 (instructional support and professional development: 20 items; supportive teaching and mentorship: 15 items; and effective mentoring and coaching: 15 items). This study has confirmed three-factor structure of the CTMS. Researchers, educators, administrators, and student teachers can use the CTMS to evaluate cooperating teachers’ mentoring skills and provide feedback on areas that need improvement.